Fitness and competitive growth comparison of methicillin resistant and methicillin susceptible Staphylococcus aureus colonies. (May 2017) - Durhan, Emine; Korcan, Safiye Elif; Altindis, Mustafa; Konuk, Muhsin
Abstract: Exponential developments of both Methicillin resistant Staphylococcus aureus (MRSA) 3R ve 36R and methicillin susceptible Staphylococcus aureus (MSSA) 27S were evaluated in the presence and absence of oxacillin. The strains were isolated from the specimens collected in microbiology department. It was also determined the transfer of mecA gene from 3R to 27S strain by using the replica plate technique. It was observed that the presence of antibiotics in the preliminary culture had a positive impact on the growth of the secondary culture of MRSA isolates. Comparison results of Rt bacteria in three different mixed cultures, assessed with Tukey's HSD test, showed a significant statistical difference among the groups. The values were as following; on the first day; Df: 2, F: 60.90, P: 0.0001, second day; Df:2, F:90.56, P: 0.0000, and third day; Df:2, F:4.86, P:0.0557. As a result of the study, we can suggest that the gene expression levels of the transferred antibiotic resistance genes could help us in both controlling hospital originated sickness and developing new strategies to prevent the spread of resistant bacteria.